Factors contributing to adaptation practice towards climate change impact among oil palm smallholders in Peninsular Malaysia - Nabara, Isah Shehu (2019)
Several existing inter-related climate phenomena and their associated impacts have contributed to the perception of oil palm smallholders in Peninsular Malaysia, making them more liable to be influenced by the resultant consequences. With a growing world population and rising living standards, palm oil demand has been projected to continue to rise in the coming decades. Oil palm smallholders in Peninsular Malaysia are generally acknowledged as being more susceptible to impacts of climate change and having less ability towards adaptation practices. Smallholders have contributed about 40 percent under oil palm smallholding schemes in the country. With the awareness of the potential and impacts of climate change, Malaysia may not be able to achieve palm oil yield target of six tons per hectare. The situation clearly shows the importance of extension services, attitude, and subjective norms among other considerations as limited studies have been conducted in this area of interest. Consequently, the present study aims at filling the voids by determining factors contributing to adaptation practices towards impacts of climate change among oil palm smallholders. The study specifically aims at determining several aspects including the levels of adaptation practices and perception of impact of climate change which encompasses extension services; attitude, and subjective norms. The study also examines the relationships between perceptions of climate change impact, extension services, attitude, subjective norms, and adaptation practices, as well as the mediation effects of intention towards adaptation practices. The study was guided by an integrated conceptual framework predominantly developed from protection motivation theory and theory of reasoning action. A structured questionnaire was used to interview 397 oil palm smallholders using a multi-stage cluster sampling technique. Descriptive analysis and structural equation modeling were applied. The descriptive findings revealed that oil palm smallholders played significant roles in adaptation practices where the majority of them were found to be engaged in adaptation practices and had good perception of impact of climate change. The majority of the respondents revealed that extension services have provided them with important sources of information and had favorable attitude in the use of adaptation practices, clearly showing that the view of others is essential in adaptation practices. The results of structural equation modeling also indicated that extension services had the highest contribution to adaptation practices. Mediating intention towards adaptation practices also played a significant role, mediating three paths. At the conclusion of the study, it was observed that adaptation practices, perception of impact of climate change, attitude and subjective norms were at both high and moderate levels. It is therefore of great significance to give greater knowledge and understanding to smallholders of the issue at hand. As a proactive measure, it is important to enhance extension services towards adaptation practices. The study proposes that the relevant government agencies such as the Malaysian Palm Oil Board (MPOB) and Federal Land Development Authority (FELDA) to come up with an extensive training model on adaptation practices and give an insight to the academicians/researchers in applying and/or improving the model while accessing other adaptation practices towards impact of climate change for future research.